Sepsis neonatorum: Bacterial profile, antimicrobial resistance patterns, among neonates and associated factors, Dilla University Referral Hospital, southern Ethiopia, with special reference to WHO prioritized pathogens - Asaye Mitiku; Aseer Manilal; Eyerusalem Asnake; Bamud Hussien; Binyam Debalke; Alayu Bogale; Zerihun Solomon; Gelila Birsaw (PLoS ONE, 2026)
Background Sepsis neonatorum (neonatal sepsis) constitutes severe, life-threatening infections, frequently necessitating intensive care unit admissions, and is a leading indication for antibiotic prescription in neonatal clinical practices. In Ethiopia, neonatal sepsis is quite rampant, and the widespread empirical therapy results in several interrelated challenges, such as incorrect or misuse of antibiotics, bacterial virulence, and aggravation of drug resistance and treatment failures. Aims This study was done to assess the culture-positive sepsis, antibiotic susceptibility patterns, and associated factors among neonates attending Dilla University Referral Hospital, southern Ethiopia. Methods A cross-sectional study was conducted from August to October 2023 among 280 neonates suspected of sepsis using systematic random sampling. Data and venous blood samples were collected and analyzed using standard microbiological procedures. Antibiotic susceptibility was tested by Kirby-Bauer disk diffusion. SPSS and logistic regression were used for analysis, with p ≤ 0.05 considered statistically significant. Results The overall culture-positive prevalence (n = 88) of neonatal sepsis was 31.4% (95% CI: 25.7, 36.8). Neonatal sepsis was predominantly caused by Escherichia coli (n = 27, 30.7%), followed by Klebsiella pneumoniae (n = 18, 20.5%). Both Gram-negative and Gram-positive bacteria were extremely resistant (80–100%) to ampicillin, amoxicillin-clavulanate, ceftriaxone, and ceftazidime. Overall, 70.2% of the isolates were multi-drug resistant, including more than a quarter of isolates that were WHO prioritized, viz., methicillin-resistant Staphylococcus aureus and extended-spectrum β-lactamase bacteria. Isolates exceeding one-fourth of the entire bacteria studied demonstrated resistance to both the first- and second-line regimens. Residence in rural areas [AOR: 1.43; 95% CI: 1.22–5.84 ( p < 0.05)], mode of delivery by Caesarean section [AOR: 3.23; 95% CI: 1.04–9.46 ( p < 0.002)], lengthy hospital stays [AOR: 4.65; 95% CI: 1.55–13.9 ( p < 0.001)], prolonged labour [AOR: 3.36; 95% CI: 1.32–8.56 ( p < 0.05)], and preterm premature rupture of membrane [AOR: 5.23; 95% CI: 4.11–9.49 ( p < 0.001)] were statistically associated with the outcome. Conclusions A substantial prevalence of culture-confirmed cases of neonatal sepsis was identified, in comparison to other regions of the country. Alarmingly, bacterial isolates demonstrated considerable resistance to the first-and second-line regimens. Regular monitoring of antibiotic resistance patterns and timely implementation of enhanced infection prevention strategies are the need of the hour.